Use of Oral Anti-Xa Inhibitor in Prosthetic Mechanical Aortic Valve with Warfarin Hypersensitivity Due to the FIX p.(Ala37Thr) Propeptide Variant: Case Report and Literature Review - Tufano, Antonella; Fierarossa, Carmine; Cirillo, Ferdinando; Miele, Ciro; Capasso, Filomena; Mazzaccara, Cristina; Micale, Lucia; Vecchione, Gennaro; Castori, Marco; Frangipane, Ignazio; Mocerino, Luca; Cimino, Ernesto; Di Minno, Matteo (Seminars in Thrombosis and Hemostasis, 2025)
Bleeding is the most common side effect during treatment with vitamin K antagonists (VKAs). Sometimes, VKA use causes bleeding episodes due to rare variants in the factor IX (FIX) propeptide that modify the affinity of FIX propeptide to the binding of γ-glutamyl carboxylase. We report on a 51-year-old patient who presented with recurrent spontaneous and severe intramuscular and cutaneous bleedings during VKA (warfarin) treatment for the presence of a prosthetic mechanical aortic valve. Laboratory evaluation revealed INR within the therapeutic range with markedly prolonged aPTT and a large reduction of FIX levels. Laboratory parameters significantly improved when warfarin was switched with low-molecular-weight heparin. Next-generation sequencing analysis revealed the variant p.(Ala37Thr) in the F9 gene, which has been previously associated with VKA sensitivity. As an alternative to warfarin, apixaban 5 mg twice daily and aspirin 100 mg daily were started, with no thrombosis or recurrence of hemorrhage and normalization of INR, aPTT, and FIX levels, at 12-month follow-up. We also performed a literature search across PubMed and Scopus, until January 2025. The analysis evidenced five case reports and two case series. The mechanisms of this rare VKA hypersensitivity have also been reviewed. In conclusion, while VKA hypersensitivity is a rare phenomenon, awareness of this complication and the current accessibility to molecular testing make it important to identify patients at risk. The efficacy/safety of direct thrombin or factor Xa inhibitors in patients with a mechanical heart valve and VKA hypersensitivity due to the F9 p.(Ala37Thr) variant deserves more attention and further investigation.
Keywords: vitamin K antagonist hypersensitivity; variant p.(Ala37Thr)in the F9 gene; DOAC